Contemporary Islamic Educational Philosophy: Integrating Ethics, Technology, and Spirituality - Farkhan Syahrul Mubarok; Roisna Kamila (Al-Munawwarah: Journal of Islamic Education, 2026)
Contemporary Islamic education faces complex challenges due to technological developments, globalization, and the dynamics of moral values in modern society. This study analyzes the philosophical thinking of contemporary Islamic education with a focus on the integration of ethics, technology, and spirituality. The research method uses a descriptive-analytical qualitative approach through a literature review of classical and contemporary sources, academic journals, and Islamic education policy documents. The results of the study show that contemporary Islamic education emphasizes a balance between moral development, the use of technology, and the strengthening of individual spirituality. The discussion underlines the importance of a philosophical framework that can bridge Islamic moral principles with technological innovation, thereby producing a generation that is not only academically competent, but also moral and spiritual. The conclusion affirms that the integration of ethics, technology, and spirituality in Islamic education is the key to shaping well-rounded individuals who are ready to face global challenges.